Representasi Budaya Pesantren dalam Film Pendek “Inthiq Rasmiyyatan” Kajian Semiotika Roland Bathes: Representation of Islamic Boarding School Culture in the Short Film "Inthiq Rasmiyyatan" A Semiotic Study by Roland Bathes - Muhammad, Sabil; Buana, Cahya; Abshar, Ulil; Abu Bakar, Irfan; Yuningsih, Yeni Ratna; Zahra, Latifah Asiyatuz (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2025)
This study aims to analyze the denotative, connotative, and mythological meanings in the short film Inthiq Rasmiyyatan produced by the students of Pondok Modern Darussalam Gontor by applying Roland Barthes’ semiotic theory. The focus of the study is directed toward the shifts in word meanings from their denotative sense to connotative interpretations that emerge through myths namely, the culture, ideology, and traditions of the Islamic boarding school (pesantren). This research employs a qualitative descriptive method with a note-taking technique centered on the film’s dialogues. The primary data include seven key lexical items: rasmiyyatan, qudam?’, mudabbir, t?j, qayyid, ???ir, and a proverb attributed to Imam al-Shafi‘i, which reflects the educational philosophy of the pesantren. The findings reveal that each term embodies three interrelated layers of meaning. Drawing on Barthes’ framework, the study uncovers that meaning is not confined to dictionary definitions but may shift contextually to represent particular values such as discipline, obedience, honor, and moral responsibility among santri (students). For example, rasmiyyatan, literally meaning “formal” or “official,” connotes linguistic discipline in using Arabic and English, while t?j (“crown”) serves as a metaphor for pride and institutional identity within the pesantren education system. At the level of myth, language functions as a representation of ideology, reinforcing the pesantren’s character, ethics, and value system. Ultimately, this study demonstrates that the film transcends mere communicative intent it portrays how language constructs social consciousness and spiritual values. Therefore, the research contributes to the advancement of linguistic and semiotic studies, while offering new insights into the role of language in shaping identity, ideology, and the educational culture of modern Islamic boarding schools